Specyfika świata przedstawionego we współczesnej dramaturgii rosyjskiej. Od ideologicznego huraoptymizmu do umiarkowanej akceptacji i krytycyzmu - Piłat, Walenty (Rusycystyczne Studia Literaturoznawcze, 2016)
The article points to the ways of creating the depicted world by the playwrights of the 80s and the 90s of the 20th century. It also indicates the next stages of the development of contemporary Russian drama, referring to the works by, among others, Yevgeni Grishkovetz, Ivan Vyrypaev, and the Presnyakov Brothers.